A descriptive study of blood films of patients serologically positive for dengue in Hospital Tengku Ampuan Afzan, Kuantan - Ismail, Rusmawati; H, Asma Hanim; Muhammad, Siti Aeshah @ Naznin; Mohd Shahid, Salman; A.Talib, Norlelawati (Faculty of Medicine, International Islamic University Malaysia, 2010)
Introduction: Dengue is one of the commonest infections in Malaysia and it is a notifiable disease. Even though the diagnosis of classical dengue fever and dengue haemorrhagic fever can be recognized clinically, the diagnosis remains a challenge in areas where it could not be differentiated with other febrile illnesses. The aim of this study was to focus on the specific and consistent morphological features observed in blood films of dengue infection. Materials and Methods: In all 400 cases of dengue infection serologically diagnosed in the Tengku Ampuan Afzan Hospital (HTAA) during May to October 2007, only a total of 27 cases had blood films examined, and thus were included in this study. These blood films were re-examined by two pathologists from HTAA. The full blood count parameters were also retrieved and studied. Results: We consistently found typical reactive lymphocytes [n= 23 (85%)] and thrombocytopenia [n=21, (77.8%)] in the cases. However, leucopenia was present only in 9 cases (33%). Conclusion: The presence of typical reactive lymphocyte is a consistent  nding in dengue fever and thus could have a significant role in supporting the diagnosis of dengue infection.